2016
DOI: 10.5812/asjsm.35201
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ramadan Fasting on Inspiratory Muscle Function

Abstract: BackgroundRamadan fasting is a major challenge for exercising Muslims especially in warm seasons. There is some evidence to indicate that Ramadan fasting causes higher subjective ratings of perceived exertion (RPE) in fasting Muslims. The mechanisms of this phenomenon are not known exactly. The role of respiratory muscle strength in this regard has not been studied yet.ObjectivesThe aim of this study was investigation of the effects of Ramadan fasting on respiratory muscle strength.Patients and MethodsIn a bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Nevertheless, among the 18 studies evaluating the effects of RF on the lung function and/or inflammatory and/or hematological data of healthy and/or asthmatics and/or COPD adults, only two achieved in India and Iran ( Askari et al, 2016 ; Singha Roy & Bandyopadhyay, 2016 ) involved control-groups. The remaining 16 studies conducted in Muslim and non-Muslim states [Iran ( Adeli et al, 2015 ; Moosavi, Kabir, Moghimi, Chehrei, & Rad, 2007 ; Norouzy et al., 2013 ; Sarraf-Zadegan et al, 2000 ; Sedaghat et al, 2017 ; Soori, Mohaghegh, Hajain, & Moraadi, 2016 ), Saudi-Arabia ( Siddiqui, Sabir, & Subhan, 2005 ; Subhan, Siddiqui, Khan, & Sabir, 2006 ); Tunisia ( Latiri et al, 2017 ; Zouari et al, 2018 ), Malaysia ( Duncan, Husain, Raman, Cheah, & Ch’ng, 1990 ), Egypt ( Abdel-aziz & Ibraheem, 2008 ), Jordan ( Al Hourani et al, 2009 ), Irak ( Baay, 2017 ), Qatar ( Bener et al, 2006 ), India ( Sayeed, Hazari, & Arifuddin, 2018 )] used Before-R or During-R data as control. Thirdly, it was desirable to assess the COPD patients’ nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, among the 18 studies evaluating the effects of RF on the lung function and/or inflammatory and/or hematological data of healthy and/or asthmatics and/or COPD adults, only two achieved in India and Iran ( Askari et al, 2016 ; Singha Roy & Bandyopadhyay, 2016 ) involved control-groups. The remaining 16 studies conducted in Muslim and non-Muslim states [Iran ( Adeli et al, 2015 ; Moosavi, Kabir, Moghimi, Chehrei, & Rad, 2007 ; Norouzy et al., 2013 ; Sarraf-Zadegan et al, 2000 ; Sedaghat et al, 2017 ; Soori, Mohaghegh, Hajain, & Moraadi, 2016 ), Saudi-Arabia ( Siddiqui, Sabir, & Subhan, 2005 ; Subhan, Siddiqui, Khan, & Sabir, 2006 ); Tunisia ( Latiri et al, 2017 ; Zouari et al, 2018 ), Malaysia ( Duncan, Husain, Raman, Cheah, & Ch’ng, 1990 ), Egypt ( Abdel-aziz & Ibraheem, 2008 ), Jordan ( Al Hourani et al, 2009 ), Irak ( Baay, 2017 ), Qatar ( Bener et al, 2006 ), India ( Sayeed, Hazari, & Arifuddin, 2018 )] used Before-R or During-R data as control. Thirdly, it was desirable to assess the COPD patients’ nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous animal samples have been designed to evaluate the longtime starvation effect on respiratory mechanic function (Harkema, Mauderly, Gregory, & Pickrell, 1984; Sahebjami & MacGee, 1985), but few human case studies have been conducted on sick (Aaron et al, 2004; Bener et al, 2006; Harkema et al, 1984; Norouzy et al, 2013; Sahebjami & MacGee, 1985; Stenius-Aarniala et al, 2000) or healthy (Abdel-aziz & Ibraheem, 2008; Duncan et al, 1990; Moosavi et al, 2007; Roy & Bandyopadhyay, 2016; Siddiqui et al, 2005; Soori, Mohaghegh, Hajain, & Moraadi, 2016; Subhan et al, 2006) subjects. In 1,590 asthmatic Muslim subjects, the FVC, FEV 1 , FEV 1 /FVC, MMEF, and PEF mean values did not identify any statistically significant differences between before-R, mid-R, and after-R sessions (Bener et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Almost 3% of Muslim patients with lung cancer ( Tas et al, 2014 ) and 93% of Turkish chronic obstructive pulmonary disease (COPD) patients ( Aydin et al, 2014 ) are Ramadan fasters. Although the relationship between religion rituals and health, and particularly the effects of RIF on chronic diseases, has been an interesting issue for physicians nearly for 30 years, this issue was only tackled in a few studies presenting controversial findings ( Abdel-aziz & Ibraheem, 2008 ; Adeli et al, 2015 ; Askari et al, 2016 ; Aydin et al, 2014 ; Bener et al, 2006 ; Duncan, Husain, Raman, Cheah, & Ch’ng, 1990 ; Erkekol et al, 2006 ; Latiri et al, 2017 ; Moosavi, Kabir, Moghimi, Chehrei, & Rad, 2007 ; Nematy et al, 2015 ; Norouzy et al, 2013 ; Siddiqui, Sabir, & Subhan, 2005 ; Singha Roy & Bandyopadhyay, 2016 ; Soori, Mohaghegh, Hajain, & Moraadi, 2016 ; Subhan, Siddiqui, Khan, & Sabir, 2006 ). Moreover, the opinions of health-care professionals and scholarly societies, concerning the effects of RIF on health, are divided.…”
mentioning
confidence: 99%
“…Several studies have observed the effects of RIF on body functions in patients with chronic conditions ( Adeli et al, 2015 ; Al-Dubeikil & Abdul-Lateef, 2003 ; Askari et al, 2016 ; Aydin et al, 2014 ; Babineaux et al, 2015 ; Bener et al, 2006 ; Bragazzi, 2015b ; M. Chamsi-Pasha & H. Chamsi-Pasha, 2016 ; Erkekol et al, 2006 ; Herrag et al, 2010 ; Nematy et al, 2015 ; Norouzy et al, 2013 ; Tas et al, 2014 ). However, studies examining the RIF effects on lung function data, are scarce, included only healthy adults or asthmatic adult patients and presented some discrepancies in their findings ( Abdel-aziz & Ibraheem, 2008 ; Adeli et al, 2015 ; Askari et al, 2016 ; Bener et al, 2006 ; Duncan et al, 1990 ; Latiri et al, 2017 ; Moosavi et al, 2007 ; Norouzy et al, 2013 ; Siddiqui et al, 2005 ; Singha Roy & Bandyopadhyay, 2016 ; Subhan et al, 2006 ; Soori et al, 2016 ). In view of the above considerations, the aim of the present pilot study was to assess the effects of RIF on spirometric data measured in male patients with a stable COPD.…”
mentioning
confidence: 99%